THE ABILITY OF THIRD YEAR STUDENTS OF SMAN 2 PEKANBARU IN COMPREHENDING FUNNY STORY - Ilham Khatib Ilham Khatib; Mahdum ' '; M.Nababan ' ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was about the ability of the third year students of SMAN 2 Pekanbaru in comprehending funny story. The objective of this study was to know how the ability of the third year students of SMAN 2 Pekanbaru in comprehending funny story is. This research was conducted at SMAN 2 Pekanbaru on October until November 2014. This is a desrciptive research. To get the data, the researcher gave a set of questions about comprehending funny story. The questions consisted of Finding factual information, finding main idea, guessing vocabulary in context, identifying references, and making interferences. After analyzing the data, the writer found that the mean of the students’ scores in finding factual information is 77, 05, finding main ideas is 80, 58, guessing vocabulary in context is 82, 94, identifying references is 69, 41, and making inferences is 84, 11. As a result there are 2 abilities in excellent level, 3 abilities in good level and the most difficult one is in identifying references and the easiest one is in making inferences. The mean of total score of the students ability in comprehending funny story is 76, 19. It means that the ability of the third year students of SMAN 2 Pekanbaru in comprehending funny story is in Good level. Keywords: Ability, Comprehending, funny story